2020
DOI: 10.1021/acs.jmedchem.0c01160
|View full text |Cite
|
Sign up to set email alerts
|

7-Hydroxycoumarins Are Affinity-Based Fluorescent Probes for Competitive Binding Studies of Macrophage Migration Inhibitory Factor

Abstract: Macrophage migration inhibitory factor (MIF) is a cytokine with key roles in inflammation and cancer, which qualifies it as a potential drug target. Apart from its cytokine activity, MIF also harbors enzyme activity for keto–enol tautomerization. MIF enzymatic activity has been used for identification of MIF binding molecules that also interfere with its biological activity. However, MIF tautomerase activity assays are troubled by irregularities, thus creating a need for alternative methods. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 62 publications
(192 reference statements)
3
29
0
Order By: Relevance
“…The K i values for the PROTACs of group 2 with a 7‐hydroxy‐3,4‐dihydrobenzoxazin‐2‐one MIF binding core were all around 100 nM. This is very well in line with the potency of their parent inhibitor 3 , which has a K i value of 150 nM [27] . The results demonstrated that our design strategy for linkers did not or minimally perturb target engagement.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The K i values for the PROTACs of group 2 with a 7‐hydroxy‐3,4‐dihydrobenzoxazin‐2‐one MIF binding core were all around 100 nM. This is very well in line with the potency of their parent inhibitor 3 , which has a K i value of 150 nM [27] . The results demonstrated that our design strategy for linkers did not or minimally perturb target engagement.…”
Section: Resultssupporting
confidence: 58%
“…The candidate PROTACs inhibited MIF enzymatic activity with nanomolar inhibition constants ( K i ). The group 1 PROTACs that contain a 7‐hydroxycoumarin MIF binding core provided K i values between 117 to 999 nM, which is in the same range as the K i of MIF inhibitor 2 that was reported to be 370 nM (Table S2) [27] . Interestingly, the PROTACs MD1 – 4 with one carbon atom between the triazole and the amide functionality are more potent MIF tautomerase inhibitors compared to PROTACs with two ( MD5 ) or three carbon atoms ( MD6 ) in this position.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Other reviews report on the use of 7-hydroxycoumarin and its derivatives in determining the activity of cytochromes P450 (CYP) enzymes [ 74 ] as well as 7-aminocoumarin derivatives in determining amino acids from serine or cysteine proteases [ 58 ]. In other cases, they are used to detect the metabolism of mitochondrial cysteines, the oxidation of which is a measure of cellular oxidative stress ( Figure 8 , compound LI ) [ 75 ].…”
Section: Discussionmentioning
confidence: 99%